GRAIN MINERAL COMPOSITION OF INTROGRESSIVE WHEAT-WILD FORMS IN BREEDING OF SPRING WHEAT ON THE NUTRITIONAL PROPERTIES - Abugalieva Aigul; Savin Timur; Cakmak Ismail; Kozhakhmetov Kenebay; Chydinov Vladimur; Morgunov Alexey (Scientific Journal of Pedagogy and Economics, 2019)
One of the most important problems of our time is providing people with balanced diet by adding all of the essential factors necessary for the health. A convenient and perspective object is interspecific and intergeneric wheat-wild hybrids that can combine nutritional, technological properties and agronomic suitability. From this point of view, introgressive forms from interspecific and intergeneric hybrids with systematic breeding of wheat type up to the F6-F8 generation are valuable with permanent forms of cytological control of 42-chromosome forms in the early generations. To use this material for practical purposes, it is necessary to characterize the mineral composition, both the metabolic potential and the biochemical composition of the grain, against a background of productivity. The content of macro- and microelements in the grain was determined by inductively-plasma-atomic emission spectrometry. The genotypes Ilinskaya x T.timopheevii (N, K, P, Zn) and Kazakhstanskaya 10 x T.dicoccum (Mg, Mn, Fe, Zn) showed stably increased level of mineral composition in the North. The genotype Kazakhstanskaya 10 x T.dicoccum in both the south and the north were characterized by a stable increase in the content of N, Mg and Fe, as well as the genotype Ilinskaya x T.timopheevii according to Zn content. It was noted the predominance of spring introgressive forms over wild and cultivated forms on the content of P, K, Mg, Fe and Ca. The obtained results indicate that in the breeding for a high level of metabolism, the use of transitional wheat-wild spring-type forms is promising for extreme continental conditions.